Selection and Engineering of Novel Brighter Bioluminescent Reporter Gene and Color- Tuning Luciferase for pH-Sensing in Mammalian Cells - Vanessa R. Bevilaqua; Gabriel F. Pelentir; Moema A. Hausen; Eliana A. R. Duek; Vadim R. Viviani (Biosensors)
Firefly luciferases have been extensively used for bioanalytical applications, including their use as bioluminescent reporters, biosensors, and for bioimaging biological and pathological processes. Due to their intrinsic pH- sensitivity, in recent years we have demonstrated that firefly luciferases can also be harnessed as color- tuning sensors of intracellular pH. However, it is known that mammalian cells require temperatures higher than 36 °C, which red-shift the bioluminescence spectra of most firefly luciferases, decreasing their activities and the resolution of ratiometric pH analysis. Therefore, we prospected and engineered novel pH-sensitive firefly luciferases for mammalian cells. We humanized the luciferases of Amydetes vivianii (Amy-Luc) and Cratomorphus distinctus (Crt-Luc) fireflies, inserted them into the pCDNA3 vector, and compared their bioluminescence and pH-sensing properties with those of Macrolampis firefly luciferase (Mac-Luc) inside fibroblasts. The transfected COS-1 with Mac-Luc and Crt-Luc displayed lower bioluminescence activity and considerably red-shifted spectra (611 and 564 nm, respectively) at 37 °C, whereas Amy-Luc displayed the highest bioluminescence activity and spectral stability at 37 °C inside cells, displaying the most blue-shifted spectrum at such temperatures (548 nm) and the best spectral resolution at different pH values, making it possible to ratiometrically estimate the pH from 6.0 to 8.0. These results show that Amy-Luc is a novel brighter reporter gene and suitable pH- indicator for mammalian cells. Furthermore, whereas at pH 8.0 the spectrum was thermally stable, at pH 6.0 Amy-Luc showed higher temperature sensitivity, raising the possibility of using this luciferase as an intracellular temperature sensor. Thus, the improved bioluminescence properties as compared to existing luciferases could offer advantages for in vivo imaging and pH- sensing for the study of mammalian cellular physiology.